Sustainable Construction Building Performance Simulation and Asset and Maintenance Management - Delgado, João M.P.Q.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book presents a collection of recent research works that highlight best practice solutions, case studies and practical advice on the implementation of sustainable construction techniques. It includes a set of new developments in the field of building performance simulation, building sustainability assessment, sustainable management, asset and maintenance management and service-life prediction. Accordingly, the book will appeal to a broad readership of professionals, scientists, students, practitioners, lecturers and other interested parties.
The use of fibre reinforced polymers in the rehabilitation of damaged masonry walletes -- Energy efficient rehabilitation measures for the Portuguese residential buildings constructed in the 1960-1990 period -- Ventilation system for drying out buildings after a flood -- Risk assessment of urban fire - Proposal of a method for analysis and management of existing building -- Building refurbishment - economical relevance of the several construction elements -- Maintenance as a tool to avoid building pathology. The Oporto building example -- An interoperable ICT tool for asset and maintenance management - Advances in research -- BIM methodology used in the maintenance of buildings -- Mechanical pathologies of reinforced concrete corbels and repair by bonding composite carbon fabrics -- Pathologies in reinforced concrete structures.
Keywords: Buildings -- Repair and reconstruction; Buildings -- Maintenance; Building materials; Cultural property; Building Repair and Maintenance; Structural Materials; Building Materials; Cultural Heritage